Taxonomía y distribución de los corales hermatípicos (Scleractinia) del Archipiélago de Revillagigedo, México - Ketchum, James T; Reyes Bonilla, Héctor (Revista de Biología Tropical, 2001)
In spite of some recent detailed accounts about the scleractinian corals of the Archipiélago de Revillagigedo, taxonomic work on this fauna has been sparse. Consequently, solid taxonomic background is needed, especially to support further studies at community level. During five field trips (between 1990 and 1995) collections were made at different depths on three of the archipelago islands: Socorro, Clarión and San Benedicto. A total of 250 specimens were collected. Coral identifications were made using co-ocurrence methods concomitant with their descriptions, diagnosis and illustrations from a number of publications, and with morphological analysis. Coral distributions were taken from literature. Twenty-two species of zooxanthellate scleractinian corals are described, with their local and world-wide geographic distribution, and each illustrated with macro and microphotographs. Keys to the genera and species of the archipelago are also included. Porites and Pocillopora exhibit the highest species richness with a great intraspecific variation, as well as a number of morphological convergences within and between species which form species complexes, and several new species and morphs. Clarion, the oldest and most isolated island of the archipelago, harbors a number of coral morphs that are probable new species. More than half of the species found at the Revillagigedos are distributed exclusively on oceanic islands of the eastern Pacific and close to one third exist only at this archipelago. The Revillagigedos have strong faunal similarities and share a number of endemics with Clipperton Atoll, all of which support the idea that these islands constitute a separate biogeographic subregion within the eastern Pacific. Lastly, the present document substantiates the hypothesis that the Revillagigedos are important steppingstone islands for the migration of in-shore marine species from the Central to the eastern Pacific